2021
DOI: 10.1111/age.13139
|View full text |Cite
|
Sign up to set email alerts
|

Study on the concordance between different SNP‐genotyping platforms in sheep

Abstract: Different SNP genotyping technologies are commonly used in multiple studies to perform QTL detection, genotype imputation, and genomic predictions. Therefore, genotyping errors cannot be ignored, as they can reduce the accuracy of different procedures applied in genomic selection, such as genomic imputation, genomic predictions, and false-positive results in genome-wide association studies. Currently, whole-genome resequencing (WGR) also offers the potential for variant calling analysis and high-throughput gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
(121 reference statements)
0
2
0
Order By: Relevance
“…Berry and others used genotypes from 89 sheep to compare two 50K SNP bead arrays and showed the genotypes were 98% concordant between the two bead arrays, showing that both bead arrays were comparable ( Berry et al, 2016 ). Another study with 31 sheep compared two 50K SNP bead arrays and SNPs identified from WGS analyzed with GATK v4.0 ( Marina et al, 2021 ). They identified similar concordance between the two arrays, 98.8% and slightly lower concordance (95.51%–97.65%) to the genotyping from WGS data ( Marina et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Berry and others used genotypes from 89 sheep to compare two 50K SNP bead arrays and showed the genotypes were 98% concordant between the two bead arrays, showing that both bead arrays were comparable ( Berry et al, 2016 ). Another study with 31 sheep compared two 50K SNP bead arrays and SNPs identified from WGS analyzed with GATK v4.0 ( Marina et al, 2021 ). They identified similar concordance between the two arrays, 98.8% and slightly lower concordance (95.51%–97.65%) to the genotyping from WGS data ( Marina et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another study with 31 sheep compared two 50K SNP bead arrays and SNPs identified from WGS analyzed with GATK v4.0 ( Marina et al, 2021 ). They identified similar concordance between the two arrays, 98.8% and slightly lower concordance (95.51%–97.65%) to the genotyping from WGS data ( Marina et al, 2021 ). However, neither study looks at the differences between which variant caller is utilized for analyzing WGS.…”
Section: Introductionmentioning
confidence: 99%